An experimental evaluation of fracture movement in two alternative tibial fracture fixation models using a vibrating platform. (May 2019) - Moazen, Mehran; Calder, Peter; Koroma, Paul; Wright, Jonathan; Taylor, Stephen; Blunn, Gordon
Several studies have investigated the effect of low-magnitude-high-frequency vibration on the outcome of fracture healing in animal models. The aim of this study was to quantify and compare the micromovement at the fracture gap in a tibial fracture fixed with an external fixator in both a surrogate model of a tibial fracture and a cadaver human leg under static loading, both subjected to vibration. The constructs were loaded under static axial loads of 50, 100, 150 and 200 N and then subjected to vibration at each load using a commercial vibration platform, using a DVRT sensor to quantify static and dynamic fracture movement. The overall stiffness of the cadaver leg was significantly higher than the surrogate model under static loading. This resulted in a significantly higher fracture movement in the surrogate model. Under vibration, the fracture movements induced at the fracture gap in the surrogate model and the cadaver leg were 0.024 ± 0.009 mm and 0.016 ± 0.002 mm, respectively, at 200 N loading. Soft tissues can alter the overall stiffness and fracture movement recorded in biomechanical studies investigating the effect of various devices or therapies. While the relative comparison between the devices or therapies may remain valid, absolute magnitude of recordings measured externally must be interpreted with caution.